2018
DOI: 10.1080/14397595.2018.1442183
|View full text |Cite
|
Sign up to set email alerts
|

Hypouricaemic effects of yoghurt containingLactobacillus gasseriPA-3 in patients with hyperuricaemia and/or gout: A randomised, double-blind, placebo-controlled study

Abstract: PA-3-containing yoghurt improves SUA levels, even in patients with hyperuricaemia and/or gout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 11 publications
2
31
0
Order By: Relevance
“…At current, only a small RCT has evaluated the effect of probiotics in patients affected with gout ( Table 1). This study showed a decrease in serum uric acid level in a subgroup of patients taking L. gasseri PA-3 over a period of 8 weeks (14). A reduction of uric acid has been demonstrated in a cohort of patients with hyperuricemia receiving two doses of L. gasseri PA-3 compared to placebo (15).…”
Section: Gout and Hyperuricemiamentioning
confidence: 59%
“…At current, only a small RCT has evaluated the effect of probiotics in patients affected with gout ( Table 1). This study showed a decrease in serum uric acid level in a subgroup of patients taking L. gasseri PA-3 over a period of 8 weeks (14). A reduction of uric acid has been demonstrated in a cohort of patients with hyperuricemia receiving two doses of L. gasseri PA-3 compared to placebo (15).…”
Section: Gout and Hyperuricemiamentioning
confidence: 59%
“…The Lactobacillus DM9218 strain also acts on the purine nucleosides (inosine and guanosine) [ 55 , 56 ]. L. gasseri PA3 has demonstrated an ability to reduce purine in foods and beverages [ 57 , 58 , 61 ]. Purines are essential to viral RNA synthesis.…”
Section: Probiotics and Immunitymentioning
confidence: 99%
“…In the study, purine biosynthesis enzyme IMPDH2, which can be reduced by L. gasseri , could interact with the viral protein nsp14. L. gasseri PA-3 reduces the absorption of the main purines contained in food, and this property has been explored as adjuvant therapy in gout and hyperuricemia [ 61 ].…”
Section: Probiotics and Immunitymentioning
confidence: 99%
See 2 more Smart Citations